THE ROLE OF MODERN WORLD CURRENCIES IN PRIVATE SECTOR - Inna Kudryashova; Marina Pleshakova (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 3, Èkonomika,Èkologiâ, 2018)
The authors compare the factors determining the scale of international world currencies transactions as saving means and means of payment. The change in the role of the US dollar, euro, pound sterling, Japanese Yen and Chinese Yuan in the private sector over the past few decades are also juxtaposed with the previous factors. The conclusion is made about an incomplete correlation of modern conditions determining the international demand for a common European and Chinese national currency, and the demand for the volumes of their use in the world. On the basis of the comparative analysis of the volumes of world currencies transactions in different spheres, the authors demonstrate the top priority of the means of payment function in the process of calling forth the demand for these means on the part of non-residents using them as payment and saving means. It is proved that the main reasons of maintaining the dominant role of the US dollar as a world currency in the private sector are the leading position of the American economy concerning its contribution into the creation of the world product, support of a relatively high level of the development of the national financial market of the USA, long-term period of the American currency being world unit of account, low operation costs concerning the operations with them and also the inertia character of private actors of the world economy. It is shown that in a short-term period in case of a further growth of the economic power of the euro zone and China, provision of a complete convertibility of the Yuan and removal of the restrictions for non-residents in the Chinese financial market and also in case of maintaining a stable economic situation in the USA, the function of the world money will be carried out mainly by the American dollar.